“Breathe, Plan, Write, and Evaluate”: the effects of an SRSD intervention and instructional feedback on 4th graders’ writing and motivation - Nunes, Andreia; Cordeiro, Carolina; Rocha, Renata; Limpo, Teresa; Castro, São Luís (Frontiers in Education, 2024)
Over the years, extensive literature attested to the value of the Self-Regulation Strategy Development model (SRSD) for writing. Additionally, feedback has been recognized as essential to the teaching and learning of writing, and as supporting evidence-based instructional models for writing. However, little is known of the effects of combining evidence-based practice models, such as SRSD, with instructional feedback, as well as with a component of meditation. The present study aimed to study the effects of an SRSD intervention and to study the importance of instructional feedback within an SRSD intervention. A total of 69 primary students (4th graders) participated in this study. The study was divided into two phases: in Phase 1, two classes participated in a SRSD intervention program (SRSD-1 group; N = 33), whereas two others received regular writing instruction (control group; N = 36); in Phase 2, the previous control group received the SRSD intervention with or without instructional feedback (SRSD-2 with feedback, N = 19, vs. SRSD-2 without feedback, N = 17, groups), while the SRSD received regular writing instruction (SRSD-1 group). The effectiveness of the intervention was confirmed in both phases for the writing outcomes variables, but not for motivation. Overall, our study showed that the SRSD intervention with an additional meditation component was effective in improving students’ writing planning for all intervention participants. Additionally, writing quality and writing structure improved among those with lower scores at the pretest. Concerning motivation, we only found an effect on self-efficacy for ideation. We expect the current research to stimulate future examinations of the value of providing students with instructional feedback in writing interventions.